Ultrasonography of multifidus muscle morphology and function in ice hockey players with and without low back pain. (May 2019) - Fortin, Maryse; Rizk, Amanda; Frenette, Stephane; Boily, Mathieu; Rivaz, Hassan
Structured Abstract: Objectives: To examine the relationship between lumbar multifidus (LM) morphology, function, echo-intensity (EI) and body composition among a group of university level ice hockey players with and withoutlow back pain (LBP). Design: Cross-sectional study. Setting: University Research Centre. Participants: Thirty-two hockey players (18 females, 14 males) participated in this study. Main outcome measures: Resting LM cross-sectional area (CSA) was assessed bilaterally at the L5 level in prone and standing using ultrasound imaging. The LM thickness at restand during contraction was evaluated in addition to LM EI. Body composition measures were acquired using dual-energy X-ray absorptiometry (DEXA) and LBP historywas acquired using a self-reported questionnaire. Results: LM muscle CSA was significantly associatedwith body composition measurements. LM EI was strongly associated with total % body fat and significantly greater in females. Resting LM muscle CSA and thickness (prone) was significantly smaller in players with LBP 4-weeks prior. LM side-to-side asymmetry (standing) was also significantly greater in players with LBP 3-months prior. Conclusion: The results provide new insights with regards to LM morphology and activation in ice hockey players and revealed specific deficits in LM morphology in athletes with LBP. LM morphology was strongly associated with body composition measurements. Highlights: Results provide novel insights on LM morphology and activation in hockey players. LM morphology was significantly associated with body composition measurements. Hockey players with LBP showed specific deficits in LM morphology. LM function (contraction) was not associated with EI or LBP.